Utilization of proteins from fishball processing washwater in fish crackers (‘Keropok’) - Yean, Yu Swee; Chai, Yeoh Kah; Motohiro, Terushige (Wiley Blackwell, 1994)
Proteins recovered from the washwater of fishball processing were used in fish crackers. Up to 10% of washwater proteins was acceptable to taste panelists. Although appearance, color and crispiness were not affected, flavor scores declined significantly when 20% and above washwater proteins were used. This was also reflected in the scores for overall acceptability. Fish crackers with 10% washwater proteins contain more protein and less fat.